Developing advanced practice nurse writing competencies as a corequisite for evidence-based practice. Issue 10 (October 2020) - Rohan, Annie; Fullerton, Judith
ABSTRACT: Writing competency is increasingly recognized as imperative for advanced practice nurses (APNs) who are engaged in evidence-based practice (EBP). Writing skills are an implied expectation inherent in many APN evidence-based practice competencies, such as "formulating evidence based policies and procedures, " and "communicates best evidence …." A quality improvement project was implemented for APN's within a post-Master's Doctor of Nursing Practice program, to create a novel set of low-cost, high-impact strategies that could be embedded into a program of study to improve APN writing skills. Prior work has indicated that mentorship and peer support are useful strategies that can contribute to the enhancement of APN writing skills. This study builds on prior work to develop a quantitative evaluation of a peer-supported writing intervention for APNs. Read Aloud innovation was one of two strategies chosen from among many writing improvement strategies identified in the literature because of easy implementation, even by faculty who lacked confidence in providing traditional writing instruction. If explicit development of writing competencies is not elevated to a higher priority in APN education, suboptimal writing confidence is likely to continue across the professional lifetime and will present as a recurring challenge for APNs who pursue higher educational degrees, transition into faculty roles, or seek to fully develop APN EBP competencies. Findings from this study indicate that feedback received from peers during the structured Read Aloud innovation, with emphasis on hierarchy of paragraph sentences (i.e., explicit examination for overarching quality of the leading sentence), is effective in improving clarity and brevity of writing among APNs.